Autoantibody:Autoantigen Competitor Decoys: Application to Cardiac Phenotypes - Cardozo, Timothy; Cardozo, Lila; Boutjdir, Mohamed (Frontiers in Immunology, 2022)
Autoimmune diseases are often associated with autoantibodies that abnormally target self-antigens (autoantigens). An intuitive therapeutic strategy for diseases caused by aAbs is to design decoys, or soluble molecules that target the antigen combining site of these aAbs, thereby blocking binding of aAb to self-antigen and subsequent tissue damage. Here, we review the known decoy molecules of these types, discuss newer technological opportunities afforded by monoclonal antibody and structural biology advances, and discuss the challenges to this approach. Recent opportunities relevant to this approach for cardiac phenotypes, specifically Ro-associated long QT syndrome, are discussed.